Perancangan Sistem Informasi Penjadwalan Mengajar Guru Berbasis Web Menggunakan Metode Algoritma Greedy - Bazlina Dini Amanda; Ananda Utami (Modem : Jurnal Informatika dan Sains Teknologi., 2024)
The development of information technology has encouraged various educational institutions to switch from manual systems to more efficient and integrated digital systems. One important activity in school management is the process of scheduling teachers' lessons, which often takes a long time and has the potential to cause scheduling conflicts when done manually. Common problems that often arise include conflicts between teachers' teaching hours, incompatibility of classroom availability, and difficulties in adjusting schedules to teachers' preferences. Therefore, this study aims to design and develop a web-based teacher scheduling information system by applying the Greedy algorithm method as a solution to optimize automatic schedule compilation. This system was developed using the PHP programming language and MySQL database with a Waterfall development model approach. The implementation results show that the system is capable of producing teaching schedules quickly, accurately, and with minimal time conflicts. Thus, the application of the Greedy algorithm has proven to be effective in improving efficiency, accuracy, and flexibility in managing teacher schedules in a school environment.